Preparation method of sphere-like porous carbon and silicon-carbon composite material

By preparing spherical porous carbon with good pore connectivity and performing nano-silicon deposition treatment, the problems of poor pore connectivity and low nano-silicon deposition efficiency in silicon-carbon materials in the prior art have been solved, thereby improving the compaction density and fast-charging performance of the material and enhancing the electrochemical performance of silicon-carbon materials.

CN121134769AActive Publication Date: 2025-12-16河北坤天新能源股份有限公司

Patent Information

Application Number
CN202511676132.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2025-12-16
Estimated Expiration
2045-11-17

AI Technical Summary

Technical Problem

Existing silicon-carbon materials prepared from spherical porous carbon have problems such as poor pore connectivity, low nano-silicon deposition efficiency, high impedance, and poor fast-charging performance.

Method used

A spherical porous carbon with good pore connectivity was prepared by mixing carbohydrate compounds with inorganic pore-forming agents, fibrous pore-forming agents, crosslinking agents and ionic liquids, followed by spray drying, pre-carbonization and activation treatment. Nano-silicon was then deposited inside the porous carbon by treating it with chlorosilane gas and crosslinking gas to form a silicon-carbon composite material.

Benefits of technology

It improves the compaction density and power performance of porous carbon, enhances the rate charge/discharge performance and cycle performance of silicon-carbon materials, and reduces the impedance and expansion of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121134769A_ABST
    Figure CN121134769A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of sphere-like porous carbon and a silicon-carbon composite material. The preparation method comprises the following steps: uniformly mixing a carbohydrate compound, an inorganic pore-forming agent, a fibrous pore-forming agent and a cross-linking agent solution, spray-drying, carbonizing, activating and pore-forming to obtain secondary particle sphere-like porous carbon, and then depositing nano silicon on the obtained material by a silane cracking method to obtain the silicon-carbon composite material. According to the obtained material, fibrous channels and granular channels in porous carbon are utilized, deposition of nanometer silicon and reduction of expansion are facilitated, meanwhile, a secondary particle structure is adopted, the intercalation and deintercalation path of lithium ions in the charging and discharging process is shortened, and the rate capability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of material preparation, and particularly relates to a preparation method of a spherical porous carbon and a silicon-carbon composite material. BACKGROUND

[0002] As a key material for preparing a silicon-carbon material, the performance of the porous carbon determines the expansion, cycle and power performance of the silicon-carbon material. The porous carbon is divided into a granular structure, a spherical structure and a perfect spherical structure according to the material morphology. The granular porous carbon has low cost and high power, but has low compaction density and low compression resistance. The perfect spherical porous carbon has high compaction density, but has large particle size, resulting in poor adhesion and poor fast charging performance. The spherical porous carbon has good contact between materials and low impedance under the condition of high compaction density, thereby improving the rate performance of the material and maintaining the compression resistance of the material, and has simple preparation and high yield.

[0003] At present, there are few silicon-carbon materials prepared by using the spherical porous carbon on the market. For example, patent application No. CN202310250745.2 discloses a spherical silicon-carbon negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: mixing a soluble ammonium salt and a carbon source solution, and then performing spray granulation, sintering treatment and pore forming treatment to obtain a spherical porous carbon, and then performing pyrolysis treatment and carbon coating treatment on the spherical porous carbon to obtain a spherical silicon-carbon negative electrode material. The carbon source is starch, and the starch includes millet starch and rice starch. The silicon-carbon material prepared by the method has a spherical morphology, but the connectivity of the pores of the porous carbon is poor, the efficiency of depositing nano-silicon is low, the deposition is uneven, and the impedance is high. SUMMARY

[0004] In order to improve the power performance and compaction density of the porous carbon and reduce the cost, the present application uses a sugar compound, an inorganic pore forming agent, a fibrous pore forming agent and a crosslinking agent to prepare a spherical porous carbon with good pore connectivity, so as to improve the power performance and reduce the expansion, and the spherical porous carbon is applied to a silicon-carbon material to improve the rate charging and discharging performance and the cycle performance.

[0005] A preparation method of a spherical porous carbon composite material, characterized in that the method comprises the following steps: A multi-hydroxyl sugar compound, an inorganic pore forming agent, a fibrous pore forming agent, a crosslinking agent and an ionic liquid are weighed according to a mass ratio of 100:1-5:1-5:1-5:100-500, and then mixed and uniformly dried by spray drying. The obtained material is pre-carbonized at 500-800 DEG C for 1-6 hours, and then heated to 900-1100 DEG C and activated and formed pores by introducing carbon dioxide gas at a flow rate of 100-500 SCCM for 1-6 hours to obtain a spherical porous carbon.

[0006] The polyhydroxy sugar compound is one of fructose, galactose, sucrose, maltose, and lactose.

[0007] The inorganic pore-forming agent is one of ammonium bicarbonate, ammonium carbonate, and ammonium chloride; the fibrous pore-forming agent is one of polyimide fiber, poly(p-benzimidazole) fiber, poly(p-phenylenebenzobisoxazole) fiber, poly(phenylenepyridinium diimidazole) fiber, and polyvinyl alcohol fiber.

[0008] The crosslinking agent is one of 2-dimethylimidazolium, 2-ethylimidazolium, 2-ethyl-4-methylimidazolium, and isopropylimidazolium; the ionic liquid is one of 1-butyl-3-methylimidazolium phosphate dihydrogen salt, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium dinitrile, 1-butyl-3-methylimidazolium bis(trifluoromethane) yellow imide salt, 1-octyl-3-methylimidazolium phosphate dihydrogen salt, 1-octyl-3-methylimidazolium tetrafluoroborate, 1-octyl-3-methylimidazolium dinitrile, 1-allyl-3-butylimidazolium dinitrile, 1-acrylpropyl-3-methylimidazolium phosphate dihydrogen salt, 1-acrylpropyl-3-methylimidazolium tetrafluoroborate, or 1-acrylpropyl-3-methylimidazolium bis(trifluoromethane) yellow imide salt.

[0009] A method for preparing a silicon-carbon composite material, characterized by comprising the following steps: Spherical porous carbon is transferred to a fluidized bed, and an inert gas is introduced to purge the air from the tube. The bed is then heated to 450℃-550℃, and a chlorosilane mixture is introduced at a flow rate of 100-500 SCCM for 30-300 min. After that, the chlorosilane mixture is stopped, the temperature is raised to 650℃-750℃, and a heteroatom gas is introduced at a flow rate of 10-50 SCCM for 30-300 min to obtain a silicon-carbon composite material.

[0010] The chlorosilane mixed gas is formed by mixing one of dichlorosilane, trichlorosilane or silicon tetrachloride with a crosslinking gas in a volume ratio of 10:1-3; the crosslinking gas is formed by gasifying one of benzoyl peroxide, diisopropylbenzene peroxide or dicarbonate peroxide.

[0011] The heteroatom gas is one of methaneborane, diborane, phosphine, and hydrogen sulfide.

[0012] Beneficial effects

[0013] 1. By mixing inorganic pore-forming agents and fibrous pore-forming agents with porous carbon precursors (carbohydrates), carbonization, and activation can generate porous carbon with round pore structures and fibrous pore structures, improving the connectivity of pores and enhancing the deposition efficiency and uniformity of nano-silicon; at the same time, as a polymer material, the carbohydrates can be polymerized and activated by heating to generate small-particle-size spherical structures, thereby increasing the compaction density of the material.

[0014] 2. Crosslinking agents can be used to crosslink porous carbon precursors. The crosslinking agent crosslinks the single-particle porous carbon precursor (carbohydrate compound) with the carbon free radical of the carbohydrate compound through the oxygen free radical of the crosslinking agent itself to form a -COC crosslinking structure, forming a secondary particle structure. The secondary particle structure has the advantage of good isotropy, which allows lithium ions to be inserted and extracted from multiple directions during charging and discharging, thereby improving rate performance and kinetic performance.

[0015] 3. By introducing a mixture of chlorosilanes and gas, the chlorosilanes decompose into Si and Cl upon heating. - H + Simultaneously, a crosslinking agent gas containing O free radicals is introduced. Oxygen free radicals have strong electronegativity and adsorb onto the carbon surface, facilitating the deposition of nano-silicon and improving silicon deposition efficiency. Meanwhile, two electronegative elements (Cl...) - O 2- Elements with higher electronegativity can steal electrons from elements with lower electronegativity to form cations and anions, which combine through electrostatic interactions. This process achieves Cl-doped porous carbon, improving electronic conductivity. Chlorosilanes are used for pyrolysis to generate nano-silicon, which is then deposited within the pores of the porous carbon, increasing specific capacity. Chlorine doping within the porous carbon further enhances the material's electronic conductivity, while heteroatoms coating and doping the exterior of the silicon-carbon material improve electronic conductivity, enhance rate performance, and reduce the contact between the core nano-silicon and the electrolyte, preventing the core nano-silicon from reacting with the electrolyte to generate gas and improving initial efficiency. Attached Figure Description

[0016] Figure 1 The image shows a SEM image of the silicon-carbon composite material prepared in Example 1. Detailed Implementation

[0017] Example 1

[0018] A method for preparing a spherical silicon-carbon composite material includes the following steps: Step S1: 100g fructose, 3g ammonium bicarbonate, 3g polyimide fiber and 3g 2-dimethylimidazole were added to 300g 1-butyl-3-methylimidazole sodium dihydrogen phosphate and mixed evenly. After spray drying, the resulting material was carbonized at 650℃ for 3h, and then the temperature was raised to 1000℃. Carbon dioxide was introduced at a flow rate of 300SCCM to activate and create pores for 3h to obtain spherical porous carbon. Step S2: The spherical porous carbon was transferred to a fluidized bed, and nitrogen inert gas was introduced to purge the air from the tube. Then, it was heated to 500°C, and a dichlorosilane mixed gas with a volume ratio of dichlorosilane:benzoyl peroxide = 10:2 was introduced at a flow rate of 300 SCCM for 150 min. After that, the introduction of the dichlorosilane mixed gas was stopped, the temperature was raised to 700°C, and diborane gas was introduced at a flow rate of 30 SCCM for 150 min to obtain a silicon-carbon composite material.

[0019] Example 2

[0020] A method for preparing a spherical silicon-carbon composite material includes the following steps: Step S1: 100g of galactose, 1g of ammonium carbonate, 1g of poly(p-benzimidazole) fiber and 1g of 2-ethylimidazole were added to 100g of 1-butyl-3-methylimidazole sodium tetrafluoroborate and mixed evenly. After spray drying, the mixture was carbonized at 500℃ for 6h. Then, the temperature was raised to 900℃ and carbon dioxide gas was introduced at a flow rate of 100SCCM to activate and form pores for 6h, resulting in secondary particulate spherical porous carbon. Step S2: Secondary particulate spherical porous carbon was transferred to a fluidized bed, and nitrogen inert gas was introduced to purge the air from the tube. The mixture was then heated to 450°C, and a trichlorosilane mixture with a volume ratio of 10:1 (trichlorosilane:diisopropylbenzene peroxide) was introduced at a flow rate of 100 SCCM for 300 min. After that, the introduction of the diisopropylbenzene peroxide mixture was stopped, the temperature was raised to 650°C, and borane gas was introduced at a flow rate of 10 SCCM for 300 min to obtain a silicon-carbon composite material.

[0021] Example 3

[0022] A method for preparing a spherical silicon-carbon composite material includes the following steps: Step S1: 100g sucrose, 5g ammonium chloride, 5g poly(p-phenylenebenzobisoxazole) fiber and 5g 2-ethyl-4-methylimidazolium were added to 500g sodium 1-butyl-3-methylimidazolium dinitrile and mixed evenly. After spray drying, the mixture was carbonized at 800℃ for 1h. Then, the temperature was raised to 1100℃ and carbon dioxide gas was introduced at a flow rate of 500 SCCM to activate and form pores for 1h, thus obtaining secondary particulate spherical porous carbon. Step S2: Secondary particulate spherical porous carbon was transferred to a fluidized bed, and nitrogen inert gas was introduced to purge the air from the tube. The mixture was then heated to 550°C, and a silicon tetrachloride mixture with a volume ratio of silicon tetrachloride:dicarbonate peroxide = 10:3 was introduced at a flow rate of 500 SCCM for 30 min. After that, the introduction of the silicon tetrachloride mixture was stopped, the temperature was raised to 750°C, and phosphine gas was introduced at a flow rate of 50 SCCM for 30 min to obtain a silicon-carbon composite material.

[0023] Comparative Example 1: Unlike Example 1, ammonium bicarbonate is not added in step S1, but everything else is the same as in Example 1.

[0024] Comparative Example 2: Unlike Example 1, in step S2, benzoyl peroxide crosslinking gas is not added to the dichlorosilane mixed gas; otherwise, it is the same as in Example 1.

[0025] Comparative Example 3: Unlike Example 1, no diborane heteroatom gas is introduced in step S3; otherwise, it is the same as Example 1.

[0026] Comparative Example 4: Unlike Example 1, polyimide fibers are not added in step S1, but otherwise the process is the same as in Example 1.

[0027] 1. SEM testing: Figure 1 The image shows a SEM image of the silicon-carbon composite material prepared in Example 1. As can be seen from the image, the material exhibits a spherical structure with a particle size between 3 and 5 μm and a uniform size distribution.

[0028] 2. Physicochemical properties of porous carbon and its coin cell testing: 2.1 Physicochemical property testing: The pore volume and pore size of the porous carbons obtained in Examples 1-3 and Comparative Examples 1 and 4 were tested according to the national standard GB / T-38949-2020 "Determination of Pore Size of Porous Membranes - Standard Particle Method". The specific surface area was tested according to the national standard GB / T38823-2020 "Silicon Carbon". The powder conductivity of each porous carbon material was tested using a four-probe tester. The diffusion coefficient of the material was tested by GITT. The test results are shown in Table 1.

[0029] 2.2 Button Cell Battery Performance Test: The porous carbon corresponding to Examples 1-3 and Comparative Examples 1 and 4 was used as the negative electrode material for lithium-ion batteries to prepare coin cells according to the following method: A binder, conductive agent, and solvent are added to the corresponding porous carbon, stirred to form a slurry, coated onto copper foil, and dried and rolled to obtain a negative electrode sheet. The binder used is LA136D, the conductive agent is SP (conductive carbon black), and the solvent is NMP. The ratio of porous carbon:SP:LA136D:NMP is 70g:15g:15g:300mL. The electrolyte is a solution with LiPF6 as the electrolyte and a concentration of 1mol / L. The solvent is a mixture of EC and DEC with a volume ratio of 1:1. The lithium metal sheet is used as the counter electrode, and the separator is a polypropylene (PP) membrane.

[0030] Each coin cell was assembled in an argon-filled glove box, and then the following performance tests were performed: Electrochemical performance test: Specifically, the electrochemical performance was performed on the Wuhan Landian CT2001A battery tester, with a charge / discharge voltage range of 0.005V to 1.5V and a charge / discharge rate of 0.1C. The discharge specific capacity and initial efficiency of the corresponding coin cell were tested, and the room temperature charge DCR (50% SOC) of the corresponding coin cell was also tested.

[0031] The test results are shown in Table 1.

[0032]

[0033] As can be seen from Table 1, Examples 1-3 have low powder resistivity and high first-pass efficiency. This is because the doping of ammonium bicarbonate and polyimide fibers in the examples creates pores, which improves the diffusion coefficient of the material, reduces material polarization, improves the first-pass efficiency of porous carbon, and reduces DCR.

[0034] 3. Physicochemical properties of silicon-carbon materials and their coin cell testing: The tap density, specific surface area, and specific capacity of the silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-4 were tested according to the methods in the national standard GB / T 38823-2020 "Silicon-Carbon". The powder resistivity was tested using a four-probe test. The test results are shown in Table 1 below.

[0035] 3.1 Button Cell Battery Test: The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-4 were used as active materials for the negative electrode sheets of the batteries to prepare and assemble seven coin cells, which were labeled as A1, A2, A3, B1, B2, B3, and B4 in sequence. The specific preparation process of each coin cell is as follows: Preparation of the negative electrode sheet: Add binder, conductive agent and solvent to the silicon-carbon composite materials (as the active material of the negative electrode sheet) corresponding to Examples 1-3 and Comparative Examples 1-4 respectively, stir and slurry, coat on copper foil, and obtain the negative electrode sheet of each battery after drying and rolling; wherein, the binder is LA136D binder, the conductive agent is SP (conductive carbon black), and the solvent is double-distilled water, and the ratio is: silicon-carbon composite material: SP: LA136D: double-distilled water = 95g: 1g: 4g: 220mL; Coin cell fabrication: The electrolyte used was a LiPF6 solution with a concentration of 1.1 mol / L. The solvent used was a 1:1 weight ratio mixture of ethylene carbonate (EC) and diethyl carbonate (DMC). A lithium metal sheet was used as the counter electrode, and polyethylene (PE) was used as the separator. The simulated battery was assembled in an argon-filled glove box. Electrochemical performance was tested using a Wuhan Landian CT2001A battery tester under the following conditions: charge / discharge voltage range of 0.005V to 1.5V, and charge / discharge rate of 0.1C. The charge DCR (0.1C, 50% SOC) and cycle performance (test conditions: 0.2C / 0.2C, 100 cycles) of the coin cell were also tested, as well as the full-charge expansion of the negative electrode. The test results are shown in Table 2 below.

[0036]

[0037] As can be seen from Table 2 above, the silicon-carbon composite materials provided in Examples 1-3 of this application have high specific surface area, low DCR, high initial discharge specific capacity, and high initial efficiency. The reason for this is that the materials in the examples have a spherical structure and doped with fibrous materials to reduce expansion, and doped with heteroatoms in the outer layer to reduce powder resistivity, reduce polarization, and improve the initial efficiency of the material.

[0038] 3.2. Soft-pack battery test: The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-4 were each doped with 90% artificial graphite as anode materials (i.e., anode sheets), with ternary material LiNi 0.8 Co 0.1 Mn 0.1O2 was used as the positive electrode material, electrolyte, and separator to assemble a 5Ah soft-pack battery. The separator of the soft-pack battery was Celegard 2400, and the electrolyte was a LiPF6 solution. The solvent of the LiPF6 solution was a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 was 1.1 mol / L. The soft-pack batteries made of silicon-carbon composite materials corresponding to Examples 1-3 and Comparative Examples 1-4 were labeled as C1, C2, C3, D1, D2, D3, D4 and their corresponding negative electrode sheets, respectively. The liquid absorption capacity and electrode resistivity of each negative electrode sheet were tested, and the test results are shown in Table 3 below. The liquid absorption capacity test process is as follows: a 1mL burette is used to draw 1mL of electrolyte, which is then dropped onto the surface of the negative electrode. The time is recorded until the electrolyte is completely absorbed, and the resistivity of the electrode is measured using a film resistance tester.

[0039]

[0040] As can be seen from Table 3 above, the liquid absorption capacity and resistivity of the negative electrode sheets made using the silicon-carbon composite materials provided in Examples 1-3 of this application are significantly better than those of Comparative Examples 1-4. The main reason may be that the specific surface area of ​​the silicon-carbon composite material provided in this embodiment increases the liquid absorption capacity of the material and the powder resistivity is reduced by the doping of heteroatoms, thereby reducing the resistivity of the electrode sheet.

[0041] This application also tested the rate performance and cycle performance of each pouch cell, and the test results are shown in Table 4 below. The conditions for the rate performance test are as follows: The charging and discharging voltage range is 2.5-4.2V, and the temperature is 25±3.0℃. Each coin cell was charged at 1.0C and 3.0C respectively, and discharged at 1.0C. The constant current ratio of charging was tested. The conditions for cyclic performance testing are: The cycle retention rate was tested at a charge / discharge rate of 1C / 1C, a voltage range of 2.5-4.2V, a temperature of 25±3.0℃, and 500 cycles.

[0042]

[0043] As shown in Table 4 above, the rate charging performance of the soft-pack battery made using the silicon-carbon composite material provided in Examples 1-3 of this application is significantly better than that of Comparative Examples 1-4. In other words, the soft-pack battery made in the examples of this application has a shorter and faster charging time. The reason may be that the examples of this application have low powder conductivity and high specific surface area to improve the rate performance of the material; at the same time, carbon fiber material is doped in the examples to reduce expansion and improve cycle performance.

[0044] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing spherical porous carbon, characterized in that, Includes the following steps: The following materials were weighed and mixed evenly: polyhydroxy sugar compound, inorganic pore-forming agent, fibrous pore-forming agent, crosslinking agent, and ionic liquid in a mass ratio of 100:1-5:1-5:1-5:100-500. After spray drying, the resulting material was pre-carbonized at 500℃-800℃ for 1-6 hours. Then, the temperature was raised to 900℃-1100℃, and carbon dioxide gas was introduced at a flow rate of 100-500 SCCM to activate and form pores for 1-6 hours, resulting in spherical porous carbon.

2. The method for preparing spherical porous carbon according to claim 1, characterized in that, The polyhydroxy sugar compound is one of fructose, galactose, sucrose, maltose, and lactose.

3. The method for preparing spherical porous carbon according to claim 1, characterized in that, The inorganic pore-forming agent is one of ammonium bicarbonate, ammonium carbonate, and ammonium chloride; the fibrous pore-forming agent is one of polyimide fiber, poly(p-benzimidazole) fiber, poly(p-phenylenebenzobisoxazole) fiber, poly(phenylenepyridinium diimidazole) fiber, and polyvinyl alcohol fiber.

4. The method for preparing spherical porous carbon according to claim 1, characterized in that, The crosslinking agent is one of 2-dimethylimidazolium, 2-ethylimidazolium, 2-ethyl-4-methylimidazolium, and isopropylimidazolium; the ionic liquid is one of 1-butyl-3-methylimidazolium phosphate dihydrogen salt, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium dinitrile amine salt, 1-butyl-3-methylimidazolium bis(trifluoromethane) yellow imide salt, 1-octyl-3-methylimidazolium phosphate dihydrogen salt, 1-octyl-3-methylimidazolium tetrafluoroborate, 1-octyl-3-methylimidazolium dinitrile amine salt, 1-allyl-3-butylimidazolium dinitrile amine salt, 1-acrylpropyl-3-methylimidazolium phosphate dihydrogen salt, 1-acrylpropyl-3-methylimidazolium tetrafluoroborate, or 1-acrylpropyl-3-methylimidazolium bis(trifluoromethane) yellow imide salt.

5. A method for preparing a quasi-spherical silicon-carbon composite material, characterized in that, Includes the following steps: The spherical porous carbon as described in any one of claims 1-4 is transferred to a fluidized bed, an inert gas is introduced to purge the air from the tube, then heated to 450℃-550℃, and a chlorosilane mixed gas is introduced at a flow rate of 100-500 SCCM for 30-300 min. Then the chlorosilane mixed gas is stopped, the temperature is raised to 650℃-750℃, and a heteroatom gas is introduced at a flow rate of 10-50 SCCM for 30-300 min to obtain a silicon-carbon composite material.

6. The method for preparing a quasi-spherical silicon-carbon composite material according to claim 5, characterized in that, The chlorosilane mixed gas is formed by mixing one of dichlorosilane, trichlorosilane or silicon tetrachloride with a crosslinking gas in a volume ratio of 10:1-3; the crosslinking gas is formed by gasifying one of benzoyl peroxide, diisopropylbenzene peroxide or dicarbonate peroxide.

7. The method for preparing a quasi-spherical silicon-carbon composite material according to claim 5, characterized in that, The heteroatom gas is one of methaneborane, diborane, phosphine, and hydrogen sulfide.

Citation Information

Patent Citations

  • Quasi-spherical silicon-carbon negative electrode material and preparation method and application thereof

    CN116161645B

  • Silicon-carbon composite microsphere anode material and preparation method thereof

    CN104362311A

  • Chitosan-based porous carbon sphere and preparation method thereof

    CN109516457A

  • Spherical-like silicon-carbon negative electrode material as well as preparation method and application thereof

    CN116161645A

  • Preparation method of silicon-carbon composite material, silicon-carbon composite material and lithium ion battery

    CN116314735A

Cited By

  • Preparation method of composite porous carbon beneficial to silicon deposition

    CN121493931A